Auditoría de gestión y su incidencia en los servicios académicos de la unidad educativa “Juan León Mera”, cantón Quevedo, año 2013 - Crespo Coello, Maira Gabriela (2015)
The research justifies its implementation as an important contribution to the educational unit "Juan Leon Mera" considering the results obtained, the same as those collected after running a performance audit, to promote the correct use of the efficiency and effectiveness of operations performed and services rendered as an institution. A general objective and specific objectives which will give us the pattern for issues that keeps the institution was raised. Within the methodology, inductive, qualitative and quantitative method was used, also developed techniques such as interview, questionnaire survey and the same internal control that were important and needed to detect the problems of the institution. In the process of the investigation we will find the various chapters that allow a better understanding of the problems of this Educational Unit. For results COSO system where the findings of which the conclusions and recommendations were obtained the same as they are issued in order to implement corrective to the weaknesses identified in internal control for the welfare and improvement of the shares obtained was used entity.